Availability Assessment of theManaging the Audit Program. According to the Specification Standard (ISO 19011:2018): A case study in Ministry of Construction Housing and General Municipalities - Abd AL-Salam, Esraa Ibrahim; Younis, Firas Raheem (Journal of Economics and Administrative Sciences, 2021)
The research aims to study the reliability of government institutions, including the audit directors, which are one of the most important oversight formations in the Ministry of Construction, Housing and Public Municipalities, on which the responsibility for comprehensive auditing of all the Ministry's (municipalities) formations falls on the Managing the Audit Program according to the specification (ISO 19011: 2018) to improve the audit performance which requires compliance with the application of the audit management system in accordance with the standard Specification (ISO 19011: 2018), depending on the methodology of the case study, and using of checklists, which were chosen accordance to the terms Which the standard specification  (ISO19011: 2018) requires,  with doing interviewing's and reviewing documents and field observations and then we have measured the extent of application and documents by relying on data collection through field coexistence and conducting interviews and viewing documents, and The Pareto chart was used by the researcher to determine the requirements most influencing In the description field  of the  international ISO19011: 2018) and the use of the chart to determine the most important Ishikawa reasons that led to get gaps, The researcher has come to the conclusion that the possibility of applying the standard (ISO19011: 2018) in part in the researched model ((Directorate)) due to material and human factors related to the lack of financial resources and human cognitive experience, which requires more work to reach the results required to implement that standard.The work in the directorate is strengthened according to international principles and standards taking place in various organizations at the local, regional and global levels which aims of ensuring sound auditing and thus reducing deviation and diffraction cases according to a specific audit system, The research depends on the latest version of the Specification Standard (ISO 19011), With a study of the reality of work in the Ministry of Construction, Housing and General Municipalities / Audit Directorate. This study is considered the first in the directorate, as the nature of its work is the closest to the specification.Paper type: research paper